A dimensão ambiental na formação profissional do assistente social - Santos, Tatiana Ferreira dos (2016)
This research aimed to understand how environmental issues are present in the initial formation of the social worker. In this sense, we tried to identify the curriculum of undergraduate courses in Social Work at the Federal University of Sergipe - UFS and the University Tiradentes - UNIT, subjects who show evidence and approaches to environmental issues; know the views of teachers on environmental relations and environmental issues; know the views of students on the educational role of the social worker from the perspective of environmental education; and identify how the environmental issue is included in pedagogical practices of teachers. The research is exploratory and qualitative approach through case study. It was used as methodological procedures document analysis of the plans of disciplines and curriculum frameworks, open questionnaires aimed at 20 students conclusive and semi-structured interviews with three teachers that include the debate on environmental issues in the disciplines. As a result of the research, it was identified two subjects in each institution, and the teachers have views on environmental issues that are based on the social totality and ecology. The views of teachers on environmental relations deal with relations of production and alienation of man over nature. The students presented critical views on the educational role of the social worker in environmental education. It is also discussed the pedagogical practices developed in the disciplines that lead to the inclusion of discussions on environmental issues in vocational training. In this sense, it unveiled that the environmental issue is present in the training of social workers in the UFS and UNIT. However, despite being present in the training, the environmental issue is discussed in only two subjects of each institution and may be extend to other curriculum subjects contemplating an interdisciplinary training. Keywords: Vocational training. Social service. Environmental issue.